THE INDONESIAN ECONOMY DURING THE SOEHARTO ERA: A REVIEW - McCawley, Peter (Masyarakat Indonesia, 2013)
At the beginning of the 1970s it was easy to believe that the road ahead for Indonesia was difficult. But as the decade unfolded, the changes across the Indonesian economy, and the sustained growth, surpassed all expectations. Numerous dramatic events seized Indonesian and international attention during the 1970s including corruption issues, the 1972 rice crisis, the Malari riots of early 1974, and the impact of the first oil boom including the Pertamina crisis. Anne Booth and I reviewed these developments in our edited collection of articles on The Indonesian economy during the Soeharto era. Looking back, our edited volume captured the excitement of the 1970s and, perhaps, was rather too cautious in looking towards the further gains that changes in the next few decades would bring to Indonesia.